The Reader in It: Henry James’s “Desperate Plagiarism” - Hivren Demir-Atay (European Journal of American Studies)
Henry James, who is often cited as the master of realism, nevertheless expresses his reservation about realist representation of love, passion, sexuality and female characters in his critical writings. This article suggests that James’s short story entitled “The Story in It” stages this situation through characters’ conversations about American and European literature. Focusing on the dynamics of storytelling, which the conversations revolve around, and particularly engaging in Barthes’s concept of “desperate plagiarism,” the article discusses the possible implications of “it” in the title of the short story. It concludes that “The Story in It” illustrates how storytelling cannot be an innocent act with its contagious nature which results in listeners/readers’ partaking in the stories told.